1999
DOI: 10.1177/030089169908500506
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevalence in the Elderly

Abstract: These figures confirm the important role of aging in determining the increase in cancer prevalence. The resulting prevalence figures clearly indicate the cancer burden placed on health care services; moreover, the figures will probably increase in the next decades due to a possible improvement in survival and to the dramatic aging of the population, assuming a stable trend for incidence rates. This picture will represent a major challenge for politicians and those dealing with health care planning and social p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…[6,7] It is the second most prevalent neoplasm in men 60 years of age or older. [8][9][10][11] Worldwide, almost 400 000 new cases are diagnosed annually with approximately 150 000 deaths. [12,13] Strikingly, bladder cancer recurrence rate is the highest among all malignancies [14] and it has the highest lifetime treatment costs per patient, of all cancers, due to its high recurrence rate and ongoing invasive monitoring requirements.…”
Section: The Bladder Cancer Burdenmentioning
confidence: 99%
“…[6,7] It is the second most prevalent neoplasm in men 60 years of age or older. [8][9][10][11] Worldwide, almost 400 000 new cases are diagnosed annually with approximately 150 000 deaths. [12,13] Strikingly, bladder cancer recurrence rate is the highest among all malignancies [14] and it has the highest lifetime treatment costs per patient, of all cancers, due to its high recurrence rate and ongoing invasive monitoring requirements.…”
Section: The Bladder Cancer Burdenmentioning
confidence: 99%
“…
117 prevalent malignant disease in elderly men owing to smoking and environmental exposures and the propensity of the urothelium for metachronous malignant tumors [1,4]. Radical cystectomy is the preferred treatment of patients with operable tumors without evidence of metastatic disease.
…”
mentioning
confidence: 99%
“…Medical research during the last decades has identified the risk factors inducing bladder cancer: age [11], gender [12], family history of BC [13], smoking [14,15,16], occupational risk [17,18,19,20,21,22] and medical risk [23,24]. …”
Section: Discussionmentioning
confidence: 99%